Economic decisions for consumers - Leet, Don R.; Driggers, Joann (Belmont, California : Wadsworth Publishing Co., 1983)
For improving consumers' decision-making skills, the authors begin by introducing some basic economic concepts in Chapter one. Chapter two deals with the forces that influence consumers' choices, values, and goals. It also introduces a decision-making model that is applied throughout the book. The next few chapters (Chapters 3 through 8) explore the factors that affect consumers' spending decisions, including stages in the individual and family life cycles, career choices, advertising, consumer protection agencies and legislation, budgeting and spending patterns, inflation, and the use of credit. Chapter nine introduces the process of comparison buying and applies it to clothing and household textiles and durables. Chapter 10 through 17 apply the decision-making skills developed earlier in the text. These later chapters cover the important consumer topics of food, energy, transportation, housing, health care, taxes, investments, life insurance, and retirement.
Includes bibliographical references and index.
ne 14/05/2018
Loans
Keywords: Consumer Education